Giving voice to problems faced by school leaders in Portugal - Espuny, Mireia Tintoré (2020)
Worldwide, leadership stories are narratives of principals facing very different problems. The purpose of this study was to identify the current problems faced by Portuguese school principals, through these actors’ voice. Nineteen public school Portuguese principals participated in this study. Semi-structured interviews were conducted, transcribed, coded, and categorised using Nvivo11 Pro. The analysis revealed that Portuguese principals have the same problems as their colleagues worldwide, but there are problems specifically related to the Portuguese educational system: problems from the process of school clustering and the leader-centred system of school management of this country. A framework to analyse the emerged problems and practical recommendations are proposed for school leaders, researchers, and policymakers to improve educational leadership